THE MYSTERY OF THE RED SUITCASE: UNCOVERING THE CRIME OF HEINOUS MURDER WITH MUTILATION - Dhevtyana Kartikasari; Yogi Prasetyo; Ferry Irawan Febriansyah (SOSIOEDUKASI, 2026)
This research focuses on the study of criminal law regulation in the positive legal system in Indonesia, as well as assessing the extent to which these regulations cover the crime of mutilation. In addition, this study also analyzes the application of the provisions of article 340 of the Criminal Code in the case of the "Red Suitcase" in Kediri with Decision Number 67/Pid.B/2025/PN Kdr. This research utilizes a normative juridical approach as the main method, namely a legal research approach that directs its main focus to the study of legal norms, legal principles, legal theories, and current laws and regulations. The results of the study revealed that until now, the crime of mutilation has not been specifically regulated in the Criminal Code. Therefore, prosecutors and judges usually apply article 338 or article 340 depending on the elements contained in the crime of mutilation. In case number 67/Pid.B/2025/PN Kdr, the defendant was tried for murder accompanied by mutilation, and was declared proven to meet all the elements listed in article 340 of the Criminal Code. As a result, the defendant was sentenced to life imprisonment as the maximum sanction other than the death penalty. This research can enrich the study of Indonesian criminal law by analyzing the legal basis of the crime of mutilation through a court decision, in the midst of the absence of special regulations regarding the criminal act.